(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2024)
In the dynamic world of business, entrepreneurial spirit serves as a driving force behind innovation, growth, and prosperity. Individuals with an entrepreneurial mindset are characterized by their proactive approach, problem-solving skills, and unwavering determination to pursue their ventures. While an entrepreneurial attitude reflects an individual’s predisposition towards entrepreneurial endeavors, entrepreneurial intention represents a concrete commitment to translate that attitude into action. An entrepreneurial attitude encompasses a constellation of positive traits that contribute to the success of aspiring entrepreneurs, such as risk-taking propensity, resilience and perseverance, creativity and innovation, problem-solving skills, and initiative and self-reliance. Meanwhile, entrepreneurial intention manifests an individual’s entrepreneurial attitude, translating a positive mindset into a concrete plan to start and operate their own business. It is characterized by business idea formulation, feasibility assessment, resource acquisition, and action orientation. This study investigated the relationship between entrepreneurial attitude and entrepreneurial intentions of BSBA students at Union Christian College. This quantitative study utilized the descriptive-correlational design and used an adapted questionnaire to gather the relevant data from 59 respondents. Regression analysis was used to determine the relationship between the entrepreneurial attitude and entrepreneurial intention moderated by their profile. The findings revealed that entrepreneurial attitude and intention were high among the participants, indicating a strong inclination towards entrepreneurial pursuits. The study also found that the demographic profile of the students did not moderate the relationship between entrepreneurial attitude and entrepreneurial intention. This study underscores the importance of nurturing entrepreneurial attitudes and intentions among business students. By providing students with the necessary support and guidance, institutions can play a pivotal role in fostering a new generation of entrepreneurs, driving innovation, and contributing to economic growth and development. In conclusion, entrepreneurial attitude and intention are critical precursors to entrepreneurial success. By cultivating these traits among business students, institutions can empower individuals to transform their entrepreneurial aspirations into reality, shaping the future of business and society.